ATM and p400 : characterisation of a novel interaction between a DNA repair enzyme and a chromatin remodeler : a thesis presented to Massey University in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biochemistry - Smith, Rebecca Jane (Massey University, 2014)
The ability to maintain genomic integrity prevents unrestricted cell proliferation and the progression of cancer. DNA repair pathways such as the DNA double-strand break (DSB) response are essential in maintaining this integrity. This system requires activation of the serine/threonine kinase ataxia telangiectasia mutated (ATM) through acetylation by TIP60, a histone acetyl transferase, and subsequent ATM autophosphorylation. During DNA repair, activated ATM phosphorylates the histone variant H2AX several kilobases either side of the break site. This phosphorylation acts a signal for additional repair proteins and chromatin remodeling complexes which repairs DNA. In a previous study, H2AX phosphorylation was induced through the over expression of TIP60 or the SWI3-ADA2-N-CoR-TFIIIB (SANT) domain of p400. It was hypothesised that over expressed TIP60 or SANT domain was able to sequester a putative negative regulator from the ATM-TIP60 complex and artificially induce activation. This study aimed to investigate if a single domain of TIP60 or if a single helix from the three helix SANT domain was responsible for the activation of the ATM-TIP60 complex. Here, the ability of the chromo domain and zinc domain of TIP60 individually and the combined zincHat domain of TIP60 to induce H2AX phosphorylation as well as three helix deletion mutants of the SANT domain of p400 was examined. While all constructs were able to be expressed in human cell lines, the induction of H2AX was variable and non-reproducible. ATM belongs to the phosphatidylinositol 3-kinase-related kinase family (PIKK). Members of the PIKK family show domain homology, where the domain of one protein is replaced with the homologous domain of another member and the function of the protein is not altered. As p400 has been previously shown to interact with TIP60 and also Transformation/transcription domain-associated protein (TRRAP), a member of the PIKK family, it was hypothesised that p400 could interact with ATM (which also interacts with TIP60). This study confirms this novel interaction between ATM and p400 through the use of co-immunoprecipitation and protein localisation using confocal microscopy. This study provides a platform to further investigate the involvement of an ATM-p400 complex during DNA repair.
Keywords: DNA repair; Ataxia telegiectasia mutated (ATM); Phosphorylation; Chromatin; TIP60; Protein kinases; Phosphoproteins